Evaluation of Entrepreneurial Skills Education Programs through the CIPP Model: Upskilling and Sustainability Challenges - Sherry Andellia; Manap Somantri; Asti Putri; Rengky Yasepta (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The Entrepreneurial Skills Education Program serves as a strategic effort to reduce unemployment and foster community economic independence through the enhancement of practical, market-oriented skills. Despite its potential, comprehensive evaluations of such programs remain limited. This study aims to evaluate the effectiveness and sustainability of the Entrepreneurial Skills Education Program using the CIPP evaluation model to identify its strengths, weaknesses, and long-term challenges. Methodology: This research employed a qualitative descriptive approach involving six participants: program managers, instructors, and participants selected through purposive sampling. Data were collected through in-depth interviews, field observations, and document analysis, and then analyzed using Miles and Huberman’s interactive model, which includes data reduction, display, and conclusion drawing. Main Findings: The results reveal that the program was designed to meet community needs and local potential, supported by a relevant and adaptable curriculum, qualified instructors, adequate facilities, and strategic business partnerships. The andragogical training process was systematically implemented, emphasizing practical learning, monitoring, and continuous evaluation. The program significantly improved participants’ entrepreneurial skills, creativity, and self-reliance, with some participants successfully generating post-training income. However, challenges persist in marketing networks and business sustainability, underscoring the need for ongoing mentoring. Novelty/Originality of this study: This study lies in the comprehensive application of the CIPP model to evaluate a community-based entrepreneurship program, an approach rarely explored in prior research. The study contributes theoretically by validating CIPP as a practical framework for non-formal education evaluation and practically by offering policy insights to strengthen entrepreneurship development and community empowerment initiatives.